Analisis Sebaran Kerawanan Banjir Menggunakan Metode Spatial Multi-Criteria Evaluation (SMCE) di Kota Pangkalpinang - Fitriansyah, Hadi; Setiawan, Fahri; Caesar, Muhammad Yusuf; Maulidya, Haya Aqilah (Mahesa Research Center, 2024)
Pangkalpinang is an area with a high potential for flood hazards. Therefore, it is essential to conduct spatial analysis to determine the flood vulnerability levels in this region. This study aims to assess flood vulnerability in Pangkalpinang City spatially. The research uses a quantitative approach with data analysis conducted through the overlay method and Analytic Hierarchy Process (AHP). The SMCE analysis results indicate that most areas in Pangkalpinang City have moderate to high flood vulnerability levels, suggesting a significant potential for flooding. Regarding dominant factors, the AHP weighting results show that land use plays a major role in determining flood vulnerability, with a weight of 0.40, meaning land use contributes 40% of the total factors. Built-up areas have a higher flood risk, explaining the high vulnerability in the city center of Pangkalpinang. Conversely, areas with low or no vulnerability are generally located in higher elevation zones with non-built-up land use, indicating that greater vegetation and higher terrain reduce the likelihood of flooding.